Physiological, Proteomic Analysis, and Calcium-Related Gene Expression Reveal Taxus wallichiana var. mairei Adaptability to Acid Rain Stress Under Various Calcium Levels - Hu, Wen-Jun; Liu, Ting-Wu; Zhu, Chun-Quan; Wu, Qian; Chen, Lin; Lu, Hong-Ling; Jiang, Chen-Kai; Wei, Jia; Shen, Guo-Xin; Zheng, Hai-Lei (Frontiers in Plant Science, 2022)
As one of the serious environmental problems worldwide, acid rain (AR) has always caused continuous damage to forestry ecosystem. Studies have shown that AR can leach calcium ions from plants and soil. Calcium (Ca) is also a crucial regulator of plant stress response, while there are few reports on how Ca regulates the response of AR-resistant woody plants to AR stress. In this study, by setting different exogenous Ca levels, we study the physiological and molecular mechanism of Ca in regulating the Taxus wallichiana var. mairei response to AR stress. Our results showed that low Ca level leads to photosynthesis, and antioxidant defense system decreases in T. wallichiana var. mairei leaves, however, these negative effects could be reversed at high Ca level. In addition, proteomic analyses identiﬁed 44 differentially expressed proteins in different Ca level treatments of T. wallichiana var. mairei under AR stress. These proteins were classified into 7 groups, including metabolic process, photosynthesis and energy pathway, cell rescue and defense, transcription and translation, protein modification and degradation, signal transduction, etc. Furthermore, the study found that low Ca level leads to an obvious increase of Ca-related gene expression under AR stress in T. wallichiana var. mairei using qRT-PCR analyses, however can be reversed at high Ca level. These findings would enrich and extend the Ca signaling pathways of AR stress in AR-resistant woody plants, and are expected to have important theoretical and practical significance in revealing the mechanism of woody plants tolerating AR stress and protecting forestry ecosystem in soil environment under different Ca levels.